Torsion of a Large Myomatous Uterus Associated with Progressive Renal Failure and Paralytic Ileus in an 86-Year-Old Woman - Guiwen Wang; Hiroshi Ishikawa; Asuka Sato; Makio Shozu (Hindawi Limited, 2019)
Uterine torsion of a nongravid uterus is rare, and proper diagnosis is challenging. Herein, we report a case of torsion of a large myomatous uterus in an 86-year-old woman who was presented with progressive renal failure and paralytic ileus. She was presented with abdominal discomfort, loss of appetite, and oliguria. A large myomatous uterus with broad calcification was identified when she underwent surgery to repair an umbilical hernia one year before the symptoms developed. Computed tomography revealed that one year later, the myomatous uterus significantly increased in size and the calcified lesion of the fibroid was largely displaced. She was also presented with paralytic ileus, and her general condition progressively worsened. Her serum creatinine levels were increased (3.5 mg/dL) and hemoglobin levels were low (8.5 g/dL). Emergency laparotomy revealed that the uterus was rotated 360 degrees clockwise at the level of the isthmus. The uterus was discolored, appearing dark red, and accompanied by broad congestion, and the cervix was elongated. The patient's renal function and ileus recovered after a hysterectomy. In conclusion, torsion of a large myomatous uterus could become life-threatening in an oldest-old woman, and early release of the torsion is necessary to avoid serious complications.